2023
DOI: 10.1007/s10639-022-11555-x
|View full text |Cite
|
Sign up to set email alerts
|

Examining the applications of intelligent tutoring systems in real educational contexts: A systematic literature review from the social experiment perspective

Abstract: Intelligent Tutoring Systems (ITSs) have a great potential to effectively transform teaching and learning. As more efforts have been put on designing and developing ITSs and integrating them within learning and instruction, mixed types of results about the effectiveness of ITS have been reported. Therefore, it is necessary to investigate how ITSs work in real and natural educational contexts and the associated challenges of ITS application and evaluation. Through a systematic literature review method, this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Intelligent Tutoring Systems (ITSs) describe computers that integrate AI into tutoring practices that know the material, the learner, and how to teach the material. 1 Moreover, ITS has also been described as an early alert system and shows no significant difference between the system and human interventions. 7 Review of the literature highlights implementation of ITSs in most educational contexts.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intelligent Tutoring Systems (ITSs) describe computers that integrate AI into tutoring practices that know the material, the learner, and how to teach the material. 1 Moreover, ITS has also been described as an early alert system and shows no significant difference between the system and human interventions. 7 Review of the literature highlights implementation of ITSs in most educational contexts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…7 Review of the literature highlights implementation of ITSs in most educational contexts. 1 Additionally, they describe how it has supported disciplines in STEM, history, and economics. Furthermore, Cognitive Tutors were identified as the primary use of the technology, and 65% of studies reported a positive effect on learning performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Artificial Intelligence (AI) has been at the center of conversations as a disruptor for many industries 1 . Within the context of education, AI as Natural Language Processing (NLP) Models have been proposed as tools to generate instructional materials, assessment grading, assistance answering questions, and providing feedback to learners [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Artificial Intelligence (AI) has been at the center of conversations as a disruptor for many industries 1 . Within the context of education, AI as Natural Language Processing (NLP) Models have been proposed as tools to generate instructional materials, assessment grading, assistance answering questions, and providing feedback to learners [2][3][4][5] . Prevalent discussion has focused on ChatGPT, an NLP Model generated by Open AI based on Generative Pre-trained Transformer (GTP) trained by textual data from the internet 2,3,6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation